VENTILATOR ASSOCIATED PNEUMONIA - Wiryana, Made (journal of internal medicine, 2007)
Ventilator Associated Pneumonia (VAP) is defined as nosocomial pneumonia that occurred 48 hours afterthe patient had a mechanical ventilation support either from endotracheal tube or tracheostomy tube. VAPussually charactherized by 3 component sign of systemic infection: fever, tachycardia and leukocytosisfollowed by new infiltrate sign or a worsening scheme on the chest x ray and bacteriologic findings of thecausal of lung infection, but acctually we can diagnosed a VAP based on the findings of a number ofcriteria: histopathologic examination of the lung tissue from an open biopsy, a fast cavity formation of alung infiltrate without any sign of tuberculosis or malignancy and a positive pleural fluid culture, in whichthe species that found on the blood culture and airway were the same.The insidens of VAP are high, according to the foreign literature approximately between 9 – 27 % from allIntensive Care Unit population. This condition made VAP as the first causal of a nosocomial infection inthe Intensive Care Unit. The mortality rate of VAP is also high, Chastre and Fagon stated that the crudemortality rate can reach of 76%. Early onset VAP which occurred on the first 4th day after admission in theIntensive Care Unit ussually had a better prognosis because of caused by a still antibiotic sensitivepathogens. The Late onset VAP which occurred after 5 days or more after hospitalization, has worseprognosis because of caused by a multidrug resistance (MDR) pathogens. In order to define the pathogensthat caused VAP, some scientist made a classification of VAP patient based on the degree of disease, riskfactor and the onset, which is the group I with mild-moderate degree, common risk factor and the onset isanytime during hospitalization or a severe degree with an early onset, ussually caused by a gram negativebacteria. The group II, patient with a mild-moderate degree, specific risk factor that happened anytimeduring hospitalization, ussually caused by all bacteria in the group I added with an anaerob bacteria. Thegroup III, patient with a severe degree, early onset with specific risk factor or a late onset, ussually caused by Pseudomonas aeruginosa, Acinetobacter sp and MRSA. Other approach is by classifying the bacteriacausing VAP in a primary endogen, secondary and eksogen type.Prevention of VAP can be done by 2 different ways, first by a non pharmachologic way, routine andstandard things that ussually done in the ICU, but this action still could not enough in lowering the insidensof VAP. Second, by a pharmachologic way, Selective Decontamination of the Digestive Tract (SSD) andOropharyngeal Decontamitation (OD). SSD is proven effective empirically in preventing VAP but the usedof antimicrobial can caused a higher risk on resistention. SDD is not recommended as a routine action inpreventing VAP so that OD with the used of antiseptic is preferred as another alternative.